Who's Your Paddy? : Racial Expectations and the Struggle for Irish American Identity - Duffy, Jennifer Nugent (Book collections on Project MUSE., 2013)
"After all the green beer has been poured and the ubiquitous shamrocks fade away, what does it mean to be Irish American besides St. Patrick's Day? Who's Your Paddy traces the evolution of "Irish" as a race-based identity in the U.S. from the 19th century to the present day. Exploring how the Irish have been and continue to be socialized around race, Jennifer Nugent Duffy argues that Irish identity must be understood within the context of generational tensions between different waves of Irish immigrants as well as the Irish community's interaction with other racial minorities. Using historic and ethnographic research, Duffy sifts through the many racial, class, and gendered dimensions of Irish-American identity by examining three distinct Irish cohorts in Greater New York: assimilated descendants of nineteenth-century immigrants; "white flighters" who immigrated to postwar America and fled places like the Bronx for white suburbs like Yonkers in the 1960s and 1970s; and the newer, largely undocumented migrants who began to arrive in the 1990s. What results is a portrait of Irishness as a dynamic, complex force in the history of American racial consciousness, pertinent not only to contemporary immigration debates but also to the larger questions of what it means to belong, what it means to be American. Jennifer Nugent Duffy is Associate Professor of History at Western Connecticut State University in Danbury, Connecticut."--